Role of flocculation aid particles in clarification of colloidal suspension using composite dry powdered flocculant - Iwata, Masashi; Shimo, Takayuki; Tanaka, Takanori; Jami, Mohammed Saedi (2016)
The clarification method by using composite flocculants in powder form has been proposed in the literature. In this study, fundamental aspects of the mechanism of turbidity removal using a composite dry powdered flocculant were investigated. The model composite flocculant comprises a mixture of inorganic flocculant (aluminum sulfate), anionic polymer flocculant, and a flocculation aid (calcium carbonate powder of 10 μm median diameter). A suspension of polymethyl methacrylate particle (PMMA, 0.15 or 0.4 μm in diameter) was used as a colloidal material. When the composite dry powdered flocculant is added to the colloidal suspension, the inorganic flocculant dissolves immediately. The polymer flocculant particles disperse well in the suspension with the help of flocculation aid particles and dissolve moderately. Flocculation aid particles play an important role; i.e. they accelerate flocculation of PMMA particles and attenuate the ability of the polymer flocculant particles to produce undissolved lumps. Since flocculation aid particles are much bigger than the colloidal particles, the aid particles act as targets for heterocoagulation of all suspended particles. The existence of flocculation aid particles in the flocculation system seems to stabilize the flocculation process. It was observed that by the usage of composite flocculant which results in clear supernatant, percentages of adsorbed polymer flocculant were nearly constant; this implies that the adsorption of polymer flocculant onto solid particles is diffusion-limited.